Developments of Special Education Policies of Various Countries: A Literature Review - Cabatay, Mulina Madlangbayan; Hermanto, Hermanto (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2022)
Special education is defined as programs that cater to children with disabilities, giftedness, and talents separately from their same-age peers. Globally, there is an increasing awareness about social inclusion which led to promoting and aiming for inclusive education for all children. This study aims to review the literature regarding the progress of special education policies in countries from various regions. Also, it seeks to answer the question, “Where do countries from different regions’ policies in special education are comparable?”. This literature review used a qualitative approach and employed thematic analysis to analyze a qualitative dataset. There are four (4) themes that emerge from the data analysis namely 1) Progress on Special Education Policies; 2) Objectives in Achieving Inclusion; 3) Inclusion as a Solution and 4) Barriers to Inclusive Education. The study suggests that various countries are recognizing inclusive education as a better way to address the needs of children with disabilities.